2020
DOI: 10.1149/1945-7111/abbb0c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Redox Processes Involved in Carbon-Coated KVPO4F for High Voltage K-Ion Batteries Revealed by XPS Analysis

Abstract: K-ion batteries need efficient positive electrode materials with open structural frameworks to accommodate the large ionic radius of K +. In that direction, polyanionic compounds are of great interest. Among them, KVPO4F is the most studied one. Its electrochemical redox processes still remain unclear, especially at high voltage. To tackle this issue, X-ray photoelectron spectroscopy was used to reveal the electrochemical redox processes of KxVPO4F. First, a carbon coating was performed and allowed increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Graphite electrodes were prepared by mixing SLP-6 graphite (Imerys Graphite & Carbon) and poly(vinylidene fluoride), PVDF (from SOLEF) with a 90:10 weight ratio, in N-methyl-2-pyrrolidone (32:68 solvent/material weight ratio), by ball-milling in an agate jar at 500 rpm for 1 h. The obtained slurry was cast on a copper current collector, dried for 24 h under Ar, and finally the electrodes were punched out and dried under vacuum at 80 °C for 12 h. KVPO 4 F electrodes (KVPF, carbon black, and PVDF with a 85:10:5 weight ratio) were prepared following a procedure previously reported. 24 In an argon-filled glovebox, 2032 coin cells were assembled using KVPF or graphite-based electrodes w/wo K-metal (Alfa Aesar, 99.95%), KVPF//graphite full cells were also prepared. For all cells, a glass-fiber paper (GF/D, Whatman) and a polypropylene−polyethylene−polypropylene membrane (Celgard) were used as separators with 100 μL of 0.8 M KPF 6 EC/DEC as the electrolyte.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphite electrodes were prepared by mixing SLP-6 graphite (Imerys Graphite & Carbon) and poly(vinylidene fluoride), PVDF (from SOLEF) with a 90:10 weight ratio, in N-methyl-2-pyrrolidone (32:68 solvent/material weight ratio), by ball-milling in an agate jar at 500 rpm for 1 h. The obtained slurry was cast on a copper current collector, dried for 24 h under Ar, and finally the electrodes were punched out and dried under vacuum at 80 °C for 12 h. KVPO 4 F electrodes (KVPF, carbon black, and PVDF with a 85:10:5 weight ratio) were prepared following a procedure previously reported. 24 In an argon-filled glovebox, 2032 coin cells were assembled using KVPF or graphite-based electrodes w/wo K-metal (Alfa Aesar, 99.95%), KVPF//graphite full cells were also prepared. For all cells, a glass-fiber paper (GF/D, Whatman) and a polypropylene−polyethylene−polypropylene membrane (Celgard) were used as separators with 100 μL of 0.8 M KPF 6 EC/DEC as the electrolyte.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…(iii) K metal polarization is nearly 0.1 V higher for 0.8 M KFSI than for 0.8 M KPF 6 , which explains the lower rate capability generally observed with KFSI EC/DEC compared to that with KPF 6 EC/DEC, especially for negative electrodes . Note that special care during K metal preparation can decrease its polarization and improve its stability over time. , In any case, electrode capacities obtained in half-cells are thus partially driven by the K metal. Overall, the use of the K metal ( i.e.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…K-ion batteries appear as a promising alternative for large-scale energy storage systems for which abundant and low-cost raw materials are required. Indeed, with the lowest (i) redox couple potential, (ii) Lewis acidity, and (iii) desolvation energy among alkali metals in nonaqueous carbonate electrolytes, potassium can enable high-voltage and high-power KIBs. Recent studies, focused on negative and positive electrode materials, showed that promising electrochemical performance can be obtained with graphite that reversibly intercalates K + into KC 8 and Prussian blue analogue or phosphate materials such as KVPO 4 F. …”
Section: Introductionmentioning
confidence: 99%
“…Polyanion-type compounds are another promising cathode for PIBs as a result of their great potential to be employed under high operating voltage. However, these cathodes usually suffer from sluggish kinetics caused by low electronic conductivity and large size of K + ions, which will lead to low reversible capacity and poor rate capability …”
Section: Surface Coating For High-energy-cathode Materials Of Pibsmentioning
confidence: 99%